2012
DOI: 10.1146/annurev-micro-092611-150154
|View full text |Cite
|
Sign up to set email alerts
|

Large T Antigens of Polyomaviruses: Amazing Molecular Machines

Abstract: The large tumor antigen (T antigen) encoded by simian virus 40 is an amazing molecular machine because it orchestrates viral infection by modulating multiple fundamental viral and cellular processes. T antigen is required for viral DNA replication, transcription, and virion assembly. In addition, T antigen targets multiple cellular pathways, including those that regulate cell proliferation, cell death, and the inflammatory response. Ectopic T antigen expression results in the immortalization and transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
126
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 106 publications
4
126
1
Order By: Relevance
“…JCV-encoded TAg plays an important role in virus replication that is similar to the role of the TAg encoded by other polyomaviruses (16,17). TAg binds to the viral origin of replication through a DNA binding domain, and the nuclear localization signal in TAg recruits TAg to the nucleus (17). The helicase domain in TAg unwinds the DNA double helix and promotes viral DNA replication (18).…”
mentioning
confidence: 98%
“…JCV-encoded TAg plays an important role in virus replication that is similar to the role of the TAg encoded by other polyomaviruses (16,17). TAg binds to the viral origin of replication through a DNA binding domain, and the nuclear localization signal in TAg recruits TAg to the nucleus (17). The helicase domain in TAg unwinds the DNA double helix and promotes viral DNA replication (18).…”
mentioning
confidence: 98%
“…SV40 LT interacts with classic partners including heat shock protein 70 (Hsc70) through the LT DnaJ domain and also interacts with retinoblastoma "pocket protein" (Rb) family members through a classic LxCxE motif in the N-terminal region of LT. SV40 LT binding of Rb abrogates its role as a repressor of E2F transcription factors, thereby promoting transition into S phase. MCV LT is thought to interact with Hsc70 and Rb via similar mechanisms (11)(12)(13). SV40 LT is also known to interact with the tumor suppressor protein p53 through two C-terminal LT regions within the helicase domain of LT (14).…”
mentioning
confidence: 99%
“…The large tumor antigen (TAg) of polyomavirus simian virus 40 (SV40) is a multidomain oncoprotein that interacts with and disrupts the function of several host proteins, thereby interfering with specific cellular pathways (11,12). TAg expression causes transformation of several primary cell types in cell culture and also induces tumors in model organisms.…”
mentioning
confidence: 99%
“…Studies investigating the mechanism of TAg-induced proliferation and transformation have shown that TAg interacts with the Rb/E2F complexes via its LXCXE motif and induces their disruption via its J-domain, thereby upregulating E2F target genes (3,13,14). Several studies have led to the current "textbook model" in which release of activator E2Fs by TAg and subsequent upregulation of E2F target genes are required for transformation (11,15). However, in view of recent studies demonstrating cell proliferation in the absence of activator E2Fs, we investigated whether TAg-induced proliferation and transformation require E2F1-2-3.…”
mentioning
confidence: 99%